Changing Ottoman Empire's Government System: Michel Foucault's Theory of Power and Modernity - Al Munawar, Faishal Agil (Pancasila International Journal of Applied Social Science, 2025)
The Ottoman Empire, which lasted for over six centuries, experienced significant political and administrative transformations, particularly in its final years. This research analyzes the transition from an Islamic Caliphate to a secular republic, using Michel Foucault's Theory of Power and Modernity as a framework. Foucault's concept of power, as embedded in social structures, helps explain the gradual collapse of the Ottoman political system, influenced by socio-political factors such as nationalism, secularism, and the decline of imperial authority. The study explores the role of power mechanisms like military control, cultural hegemony, and administrative reforms in this transformation. Adopting a normative, descriptive-qualitative approach, the research follows four stages: data collection, reduction, presentation, and conclusion. The findings suggest that the Ottoman Empire’s decline was shaped by both external pressures and internal shifts in how power was exercised. The study underscores the importance of Foucault’s concepts in understanding the empire’s modernization and eventual collapse, offering a deeper perspective on the shift from an Islamic Caliphate to a secular republic.